The Experimental Study Of Wekondo Materialsplite And Sand Of Poni-Poniki District Tirawuta East Kolaka Regency As Material Of Concrete Making - Mansyur Mansyur (NAROTAMA UNIVERSITY, Indonesia)
Split Material derived from Wekondo and Sand found in Poni-Poniki is an abundant material that has the potential to be used as a material for making concrete. The purpose of this research is to find out whether Wekondo split material and Poni-poniki sand can be used in making concrete both in terms of material characteristics and the quality of concrete achieved. This research is experimental by testing material characteristics as well as the making of 150 mm sized concrete cube test object on applicable SNI. The result of the test of the characteristic of Split material such as filter analysis at # 3/8 exceeds the specification of 6.25%, aggregate wear19,639%, pass filter sieve # 200 is 0.772%, specific gravity (SSD) 2,913 gr / cm3, 1.363%, 0.628% moisture content of 1.7kg / ltr solid content and 1.469kg / ltr of loose fill weight. While the examination of a sand material of Poni-poniki analyzed sieve all meet the standard specification, pass filter sieve # 200 is 1,680%, density of 2.661 gr / cm3, aggregate 1.647%, moisture content 0.580%, / ltr the loose weight of 1.531kg / ltr. While in concrete compressive strength test, the age of 7 days is 203,68 kg / cm2, and age 28 day is 257,55 kg / cm2. From the results of the study showed that the compressive strength at the age of 28 days can achieve K-250 quality.